PEMENUHAN HAK ASI EKSKLUSIF DI KALANGAN IBU BEKERJA: PELUANG DAN TANTANGAN (FULFILLING THE RIGHT FOR EXCLUSIVE BREASTFEEDING AMONG WORKING WOMEN: OPPORTUNITIES AND CHALLENGES) - Angga Sisca Rahadian (Research Centre for Population, Indonesian Institute of Sciences, 2014)
Women participation in the business today cannot be neglected. Demographic data shows that the proportion of women in the total labor force from year to year is exhibiting an upward trend. The data also shows that approximately 66% of the working womens are at their reproductive age. Given on these circumstances, the aim of this paper is to study challenges as well as opportunities of fulfilling the right for exclusive breastfeeding among working women. This study uses data from in-depth interview of workingwomen and direct observation in office environment. The study found that the number of workingwomen able to do exclusive breastfeeding is still far from the expectation. On this founding, the study identified that the lack of support from both physical and social environments is the major reason. Most of respondents have not lactation room in their office and if they want to express the milk, they have to use inproper room, even in the toilet. In addition,they did not get support from their colleagues and it can influence the production of milk. Meanwhile, based on PP No. 33 Tahun 2012 about ASI Eksklusif states that workplace have to provide lactation room for their employee who breastfeed. The recommendation of this study are (1) autorized institution have to encourage workplace to provide the lactation room and the support facilities according to their financial ability (2) The workplace should make a campaign about exclusive breastfeeding with posters or brocures so it can increase awareness and knowledge to support ASI Eksklusif program (3) a strict sanctionmust be applied for the workplace which do not provide lactation room.